A Gothenburg Papyrus and the Letter to Abgar - Youtie, Herbert C. (Harvard theological review, 1930)
The resemblance of P. Got. 21 to the letter sent by Jesus to Abgar had already occurred to me when I saw Bell's review of Frisk's publication. Bell there expresses the opinion that “the text looks like a version of the ‘Letter to Abgar.’” It is in reality nothing else.